Automated Analysis of Cell Surface Ruffling: Ruffle Quantification Macro - Nicholas Condon; Jennifer Stow; Adam Wall (Bio-Protocol, 2020)
Cell surface protrusions include F-actin rich, wave-like ruffles that are erected transiently in response to stimuli and during cell migration. Macrophages are innate immune cells that ruffle constitutively and more dramatically in cells activated by pathogens. Dorsal ruffles and their resulting macropinosomes are key sites for environmental sampling, pathogen detection and immune signaling. Quantitative assessment of ruffling is important for assessing pathogen responses in macrophages and for analysis of growth factor responses in other cell types but automated and quantitative methods are lacking, and rely on manual and qualitative assessments. Here we present an automated ImageJ macro for quantifying dorsal cell surface protrusions from 3D microscope images. The assay presented here is suitable for high-throughput screening applications to detect drug, pathogen, or growth factor induced changes in cell ruffling by measuring ruffle area and intensity and providing normalized values in an easy to read combined spreadsheet.